APPLICATIONS OF COSMOGENIC NUCLIDES TO LAURENTIDE ICE SHEET HISTORY AND DYNAMICS - Briner J.P.; Gosse J.C.; Bierman P.R. (My University, 2006)
Ice sheets play a fundamental role within Earth's climate system and in shaping landscapes. Despite extensive research, the maximum extent and basal dynamics of the Laurentide Ice Sheet (LIS) during the last glacial cycle remain elusive and debated in many areas. Recently, cosmogenic nuclides (e.g., 36Cl, 26Al, 10Be) have played an important role in improving our understanding of LIS extent and behavior. Applications of cosmogenic nuclides to LIS research include surface exposure dating of glacial features, constraining magnitudes of glacial erosion, addressing long-term subaerial exposure and ice sheet burial histories, and burial dating of glacial sediments. These techniques have contributed to the depiction of a more extensive LIS than previously reconstructed for the Last Glacial Maximum. In addition, cosmogenic nuclide research has definitively shown that the LIS covered intensely weathered terrain along its deeply dissected eastern margin, where there were steep gradients in the effectiveness of basal erosion related to basal thermal regime. Cosmogenic nuclide applications, those already employed as well as those yet to be discovered, will undoubtedly continue to contribute to our ever-improving understanding of ice sheet history and dynamics.
Keywords: COSMOGENIC NUCLIDE; ICE SHEET DYNAMICS; ICE SHEET HISTORY; LAST GLACIAL MAXIMUM; LAURENTIDE ICE SHEET